2007
DOI: 10.1007/s11695-007-9066-6
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Aggregation and Deformability among Patients Qualified for Bariatric Surgery

Abstract: Obesity is associated with RBC rheological disturbances expressed by a decrease in RBC deformability, increased total aggregation extent and the alteration of kinetics of RBC aggregation. These results may suggest the necessity of introducing treatment forms to correct erythrocyte rheological properties, which may improve the blood-flow condition in the microcirculation and prevent postoperative complications after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In the study carried out by Wiewiora et al [31] in 40 patiens qualified for bariatric surgery in whom ED was measured with the LORCA (Laser-assisted optical rotational cell analyzer), a similar device as the Rheodyn SSD used in the present study, ED was found to be decreased when compared with a normalweight group. The authors only performed the Pearson bivariate correlation between ED and several lipidic parameters, founding a correlation between ED and TG although they did not indicate whether the correlation was positive or negative.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In the study carried out by Wiewiora et al [31] in 40 patiens qualified for bariatric surgery in whom ED was measured with the LORCA (Laser-assisted optical rotational cell analyzer), a similar device as the Rheodyn SSD used in the present study, ED was found to be decreased when compared with a normalweight group. The authors only performed the Pearson bivariate correlation between ED and several lipidic parameters, founding a correlation between ED and TG although they did not indicate whether the correlation was positive or negative.…”
Section: Discussionsupporting
confidence: 46%
“…In this sense, most studies have been performed in patients with obesity grade I or II with conflicting results [2,7,10,12,16,19,20,28,33]. However, scarce information exists regarding ED in patients exclusively with morbid obesity [13,31,32]. In this respect the authors [31] have found a decreased ED but the cause is uncertain, as no multivariate regression analysis that allow to know the independent association of diverse parameters with ED have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Valensi confirmed a decrease of erythrocyte deformability expressed in the RBC index of filtration in normotensive and hypertensive obese patients compared to controls, but there were no significant differences between both obese groups [18]. The results of our previous study showed that obesity is associated with RBC rheological disturbances expressed by a decrease in RBC deformability, increased total aggregation extent and the alteration of kinetics of RBC aggregation [20]. Disturbances of RBC aggregation (aggregation index and aggregation half-time) were especially marked in diabetic obese patients.…”
Section: Discussionmentioning
confidence: 55%
“…However, there was no such relationship between other rheological properties and waist/hip ratio. The studies showed no differences in plasma viscosity and red blood cell filterability between android and gynoid obese women [20]. Another study also confirmed that erythrocyte aggregation index and plasma viscosity was similar regardless of WHR differences [14].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation